LINGKUNGAN EKSTERNAL PENDIDIKAN (GLOBAL, NASIONAL, DAN LOKAL) - AS, Moh Fayyad; Hadi, Saiful (STKIP Pesisir Selatan, 2025)
This study aims to examine the external environment of education from global, national, and local perspectives. The research employs a descriptive qualitative approach through a literature review by analyzing books, journal articles, and previous studies related to the external environment of education. The focus of the study is the external educational environment viewed from the dimensions of globalization, national context, and local culture. The findings indicate that the external environment of education comprising global, national, and local aspects simultaneously influences the direction and quality of educational implementation. At the global level, the flow of globalization, technological advancement, and international competency competition require educational systems to adapt and innovate. At the national level, education is shaped by government policies, national cultural values, and developmental needs aimed at improving the quality of human resources. Meanwhile, at the local level, community characteristics, regional culture, and local wisdom serve as important factors in creating relevant and contextual learning. The results show that synergy among these three external environments is essential to develop an adaptive, character-driven educational system capable of responding to contemporary challenges.